Protonation‐Induced Chirality Drives Separation by Differential Ion Mobility Spectrometry. Issue 9 (14th January 2022) - Ieritano, Christian; Yves Le Blanc, J. C.; Schneider, Bradley B.; Bissonnette, Justine R.; Haack, Alexander; Hopkins, W. Scott
Abstract: Upon development of a workflow to analyze (±)‐Verapamil and its metabolites using differential mobility spectrometry (DMS), we noticed that the ionogram of protonated Verapamil consisted of two peaks. This was inconsistent with its metabolites, as each exhibited only a single peak in the respective ionograms. The unique behaviour of Verapamil was attributed to protonation at its tertiary amino moiety, which generated a stereogenic quaternary amine. The introduction of additional chirality upon N‐protonation of Verapamil renders four possible stereochemical configurations for the protonated ion: ( R, R ), ( S, S ), ( R, S ), or ( S, R ). The ( R, R )/( S, S ) and ( R, S )/( S, R ) enantiomeric pairs are diastereomeric and thus exhibit unique conformations that are resolvable by linear and differential ion mobility techniques. Protonation‐induced chirality appears to be a general phenomenon, as N ‐protonation of 12 additional chiral amines generated diastereomers that were readily resolved by DMS. Abstract : Ionization of N ‐protonated Verapamil by electrospray ionization (ESI) yields two peaks when measured by differential mobility spectrometry (DMS). This strange behaviour is caused by protonation‐induced chirality, whereby protonation of Verapamil's tertiary amino moiety during ESI generates diastereomers that can be resolved in the gas phase.